(untitled) (Colombia Medica, 2010)
Introduction: This study shows the relaxant effect induced by ayanin in aorta rings from Wistar rats linked to nitric oxide/cyclic-GMP pathway. This flavonoid is the prevalent compound obtained from Croton schiedeanus Schlecht (Euphorbiaceae), specie used in Colombian folk medicine for the treatment of arterial hypertension. Objectives: To identify possible action mechanisms of vascular relaxation induced by ayanin (quercetin 3,4’,7-trimethyl ether). Methodology: Isolated aorta rings from Wistar rats obtained at the Animal House of the University of Salamanca were contracted with KCl (80 mM) or phenylephrine (PE, 10-6 M) and exposed to ayanin (10-6-10-4 M). Then, the effect of ayanin was assessed in deendothelized rings contracted with PE and in intact rings contracted with PE previously incubated with: ODQ (10-6 M), L-NAME (10-4 M), L-NAME plus D- and L-arginine (10-4 M), indomethacin (5x10-6 M), dipyridamole (3x10-7 M), glibenclamide (10-6 M), propranolol (10-6 M), verapamil (10-7 M) or atropine (3x10-5 M). In addition, the relaxant effect of acetylcholine (Ach, 10-8-3x10-4 M), and sodium nitroprusside (SNP, 10-9-3x10-5 M) was assessed in the presence and absence of ayanin (10-6 M). Results: Ayanin induced a greater concentration-dependent relaxation in vessels contracted with phenylephrine (pEC50: 5.84±0.05), an effect significantly reduced by deendothelization and by both ODQ and L-NAME. L-arginine was able to reverse the effect of L-NAME. Indomethacin weakly inhibited ayanin response. Dipyridamole, glibenclamide, propranolol, verapamil, and atropine did not affect ayanin relaxation. Ayanin did not have any effect on the relaxation elicited by acetylcholine (ACh), while weakly decreasing the relaxation induced by sodium nitroprusside (SNP). Conclusion: Ayanin induces endothelium-dependent relaxation in the rat aorta mainly related to nitric oxide/cGMP pathway, according to the response observed in the presence of L-NAME, L-arginine and ODQ.